On the Art of Fighting: A Humanist Translation of Fiore dei Liberi's Flower of Battle Owned by Leonello D'Este - Mondschein Ken (Bern Open Publishing, 2018)
The author presents a study of Bibliothèque National de France MS Latin 11269, a manuscript that he argues was associated with the court of Leonello d'Este and which represents an attempt to "fix" or "canonize" a vernacular work on a practical subject in erudite Latin poetry. The author reviews the life of Fiore dei Liberi and Leonello d'Este and discusses the author's intentions in writing, how the manuscript shows clear signs of Estense associations, and examines the manuscript both in light of its codicological context and in light of humanist activity at the Estense court. He also presents the evidence for the book having been in the Estense library. Finally, he examines the place of the manuscript in the context of the later Italian tradition of fencing books. A complete concordance is presented in the appendix.